If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(1 + -1n) = 6 + -6n (1 * -3 + -1n * -3) = 6 + -6n (-3 + 3n) = 6 + -6n Solving -3 + 3n = 6 + -6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6n' to each side of the equation. -3 + 3n + 6n = 6 + -6n + 6n Combine like terms: 3n + 6n = 9n -3 + 9n = 6 + -6n + 6n Combine like terms: -6n + 6n = 0 -3 + 9n = 6 + 0 -3 + 9n = 6 Add '3' to each side of the equation. -3 + 3 + 9n = 6 + 3 Combine like terms: -3 + 3 = 0 0 + 9n = 6 + 3 9n = 6 + 3 Combine like terms: 6 + 3 = 9 9n = 9 Divide each side by '9'. n = 1 Simplifying n = 1
| 10(v+2)-4v=3(2v+1)-12 | | 17-5(-7-8)+1= | | b-34=11 | | 6x+29=-4x | | 500+35g=55h | | w+-30=-52 | | 34=y-18 | | 7y=-98 | | b+13=42 | | -56=74+10x | | -3(2x-2)=24 | | 8t-10-2t=-6+10+9t | | 6y+3x=22 | | x+10(x+1)+5=550 | | 2y+4x=12.50 | | a^2+6a=7 | | -(5-3x)+x=4 | | 2r^3+8r^2+6r=0 | | -3.4x=36 | | x+64=x+59 | | x+64+x+59=75 | | -53=90-11x | | x+64+x+59+75=180 | | 18+6g=2(4c+5) | | 5.9x-1=12.7+6.2 | | -6-3(2k+4)=14 | | 3(a-4)=-21 | | 3y^2+3y-18=0 | | 12r-9=6r+18 | | 15=a+24 | | 7m-17=6 | | -28=p+2 |